Material Culture and Social History in Early Medieval Western Europe - Garver, Valerie L. (History compass, 2014)
Historians of the early Middle Ages (c. 600-c. 1050) have long used material remains and archeological evidence to learn about that era. Over the last four decades, material culture studies have become a prominent area of historical research, particularly for cultural historians. Recent early medieval studies have followed this trend. In addition, religious and economic studies of the so-called "Dark Ages" have drawn from material sources. Object-driven social history has been less popular, but recent work, especially on Francia and Anglo-Saxon England, demonstrates that such projects offer new findings on a period whose texts rarely address social relations and everyday life directly. Material culture therefore offers rich research possibilities for early medieval social history.